Pengaruh Insentif Terhadap Kinerja Guru Pada Sekolah Menengah Atas Negeri (SMAN) Dengan Motivasi Sebagai Variabel Intervening - Cornelius Pasaribu; Irsutami Irsutami (Politeknik Negeri Batam, 2015)
The purpose of this researdh is to examine the influence of materiil incentive for teacher performance SMAN with motivation as intervening variable for mainland area in Batam. The number of teachers who used as responen is 203 and the analytical methods are simple and multiple regression, path analysis (path analysis), and Sobel test to examine the influence of intervening variables. The result showed that partially materiil incentive an affect toward motivation but don’t affect toward performance, while the motivation an affect toward performance. Another result from this study showed that motivation indirectly can affect in relationship of materiil incentive and teacher’s performance. This result describe that giving an incentive could improve teacher’s motivation especially increase self potential to achieve a good performance.